Compartilhamento de custos e crédito estudantil contingente à renda: Possibilidades e limitaç\~oes de aplicaç\~ao para o Brasil - Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The contemporary debate on postsecondary student funding involves two key issues: a) fiscally responsible ways to allocate more resources to public institutions, as by increasing student participation on the costs of their studies in a manner that avoids additional barriers to access; b) design of student aid programs emphasizing equity goals, while limiting the amount of public subsidies. These are usually poorly discussed topics in the Brazilian context. Nonetheless, the current scenario of fiscal restriction and deteriorating economic indicators may bring to light topics such as cost sharing in public universities and the provision of income contingent loans (ICL). This paper presents a literature review on ICL, which are little known in Brazil, and discusses possible ways to implement them in the Brazilian context. The major objective is twofold: i) to introduce a research agenda on cost sharing in public higher education institutions; ii) to propose a reformulation of the existing federal student aid program designed for low-income students enrolled in private institutions. Besides that, ICL and equity-like financial instruments are briefly discussed as alternatives to: iii) expand the availability and decrease the costs of loans to finance student living costs; iv) finance professional certificates and postgraduate courses. This paper is an initial approach to these issues, yet to be further developed in future studies.
Keywords: I22; H81; H52; 330; student funding; postsecondary education; Brazil; income contingent loans